Cellular benign fibrous histiocytoma of the skin. - Ingravallo, G. (European Journal of Pediatric Dermatology, 2022)
Benign fibrous histiocytoma (BFH) is one of the most frequent mesenchymal tumors of the skin; it is usually localized in the dermis. However, it can also affect the subcutaneous (5). BFH almost always has a benign course and the relapse rate is less than 2% (4), but it is higher in some of its variants, such as cellular BFH (3). The cellular variant prefers young adults and the male sex; its most frequent location is the upper limb and the shoulder girdle; its diameter usually does not exceed 2.5 cm. The cellular variant relapses locally in 26% of cases (3). From the histological point of view, one third of cases extends to the subcutaneous fat tissue and 12% of cases present foci of cell necrosis; cellular polymorphism is always present and the mitotic index is never high (3). (...).